Construction Complex Development Influence on Region Social and Economic Security - Varnaliy, Zakhariy; Onyshchenko, Svitlana; Zavora, Taina (International Journal of Engineering and Technology, 2018)
Construction complex development influence on region social and economic security is studied, taking into account Ukrainian housing stock development main indicators peculiarities and general population housing provision in the regions. Region construction complex development influence on region social and economic security level has been investigated based on correlation-regression analysis. It is emphasized that regional inter-sectoral complexes, in particular, construction, are influence subject to many factors, threats and dangers for the socio-economic life of the region and need to function safely.Â Region social and economic security assessing methodical principles, taking into accountÂ  construction complex development criteria, have been proposed, and made it possible to form indicators system using the integral method and their threshold values, taking into account the complex hierarchical links with region social and economic development in particular and the state as a whole.Â